2016
DOI: 10.1016/j.ecresq.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Infant child care quality in Portugal: Associations with structural characteristics

Abstract: This study examines the quality of infant center care in Portugal through a multimeasure approach and investigates the associations among process quality dimensions and structural quality indicators. Ninety infant child care classrooms were observed during two full mornings with the ITERS-R, the CLASS-Infant and the CIS. Results revealed that a two-factor structure of process quality with the domains (a) Relationships and (b) Use of Space and Materials provided the best fit to the data. Of the structural indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…In Portuguese infant toddler centres, no differences were found in process quality regarding for-profit or non-profit centres (Barros and Aguiar, 2010 [74] ). However, a US study revealed that non-profit provision scored higher on a number of quality features, including health, safety and furnishing and aspects related to provisions for staff, but no differences were found for the quality of interactions (King et al, 2016 [114] ).…”
Section: Type Of Centrementioning
confidence: 99%
See 2 more Smart Citations
“…In Portuguese infant toddler centres, no differences were found in process quality regarding for-profit or non-profit centres (Barros and Aguiar, 2010 [74] ). However, a US study revealed that non-profit provision scored higher on a number of quality features, including health, safety and furnishing and aspects related to provisions for staff, but no differences were found for the quality of interactions (King et al, 2016 [114] ).…”
Section: Type Of Centrementioning
confidence: 99%
“…Smaller ratios and group size have been found to be related to higher overall process quality in the United States, China and Portugal (Barros and Aguiar, 2010 [74] ; Burchinal et al, 2002 [75] ; Hu et al, 2016a [64] ; Mashburn et al, 2008 [76] ; Philips et al, 2000 [77] ; Phillipsen et al, 1997 [78] ) and with responsive, warm and positive staff-child relations in particular (Burchinal et al, 2002 [75] ).…”
Section: Early Childhood Education and Care Classroom Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the 14 articles selected for this review sheds light on aspects related to a positive classroom climate that can be categorized as "static" aspects, such as grouping, materials or decorative elements, or "dynamic" aspects, such as time or the quality of instruction, teacher-children interactions, and relationships with family members. These aspects can be grouped under the two dimensions that have been agreed upon in the literature to define quality in early childhood education: "structural aspects" and "pedagogical practices" (Andrews et al 2014;Barros et al 2016;Løkken et al 2018;Mathers et al 2014). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is broad acceptance that quality in childcare services can be addressed by examining two commonly accepted components-structure and process (Howes and Rubenstein, 1983;Penn 2011;Phillipsen et al 1997;Beller et al 1996). Structural quality refers to components such as physical environment (buildings, space and materials), childstaff ratios, staff education and training, and curriculum that are more easily measurable in determining quality (Barros et al 2016;Slot et al 2015;OECD 2006). Process quality focuses on the nature of interactions between the children and teachers, among children, and among adults-teachers, parents, staff, and on the nature of leadership and pedagogy (Barros et al 2016;Slot 2017;Thomason and La Paro 2009;Vandell and Wolfe 2000a;Cryer 1999;Goelman et al 2006).…”
mentioning
confidence: 99%